PERSEPSI MAHASISWA FISIP UNDIP TERHADAP PROFIL KABINET KERJA JOKOWI - Rina Martini (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Success or failure of the new government 2014-2019 period, one of which depends on how the performance of his cabinet. The new cabinet period 2014-2019, is a cabinet that must work in a condition where people are getting good at providing an assessment of the cabinet. Student perceptions Fisip Undip Against Working Cabinet Jokowi stated that the average (50%) the performance of cabinet work in politics, law, economics, and foreign, is not good. Minister of most preferred is Anis Baswedan, Minister of Culture, Primary and Secondary Education. And most preferred is Puan Maharani. Minister corresponding position with educational background is Anis Baswedan. While that does notfitis Puan Maharani. Looking forward to the Labour cabinet Jokowi is: free Collusion, Corruption and Nepotism, avoiding politicization, and soon ful fill his campaign promises.